The right to informed choice in nanofood consumption in Malaysia / Muhammad Iqram Zulkupri - Zulkupri, Muhammad Iqram (2022)
The usage of nanotechnology has seen increased emergence of products ranging from the health care industry to food industry. Food that undergoes the nanotechnology process is known as nanofood. Studies have established that the presence of engineered nanomaterials (ENMs) in food is associated with both benefits and risks. With regards to its benefits, consumers can now enjoy greater improvement of the food products in term of its texture, food appearance, and food shelf. However, as these benefits associated with risks, consumers are also exposed with potential health implications emerge from the consumption of nanofood products, such as exposure to an increased production of oxyradicals, oxidative damage to the cell, and risk for bioaccumulation within the human body. At present, there is an absence of right to an informed choice for consumers in the Malaysian legal framework in relation to nanofood consumption. Neither food legislation nor consumer protection legislation provide for consumers to be informed on the presence of ENMs in the food sold. This has resulted in consumers were unable to make decision whether to consume nanofood especially owing to the risks posed by nanofood. In the European Union (EU), legislative reform of the nanofood consumption has occurred to provide a higher level of protection to their consumers. The legislative reform has accorded the EU consumers with the right to an informed choice in nanofood consumption. This study aims to propose that Malaysian consumers must be accorded with the right to an informed choice in nanofood consumption as a mean of protection to the consumers.